2020
DOI: 10.3390/en13164165
|View full text |Cite
|
Sign up to set email alerts
|

Series of Combined Pretreatment Can Affect the Solubilization of Waste-Activated Sludge

Abstract: Various pretreatment methods have been combined and employed for maximizing the solubilization of waste-activated sludge (WAS). However, the question “by changing the series of applied combined pretreatments (CPs), can the solubilization efficiency of WAS be affected?” has never been addressed. In this study, firstly, thermal (T), alkaline (A), and ultrasonic (U) pretreatments were individually applied at broad strengths (T = 80–120 °C for 30 min, A = pH 9–12, and U = 5–60 min at 300 W). Then, pretreatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Although the pretreatment methods are commonly applied individually as standalone procedures, the sequential or simultaneous application of some different methods has also been scrutinized [9]. The combined pretreatment has been of high popularity owing to better efficiencies in terms of sludge hydrolysis, solubilization of organic constituents, biogas and methane yield, compared to when these methods are applied alone [54,161,[200][201][202]. Additionally, coupling of single pretreatments in some cases, enables the improvement of some limitations that occur during the implementation of individual methods, which are usually associated with increased energy consumption, high capital, investment and operation costs [12].…”
Section: Combined Pretreatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pretreatment methods are commonly applied individually as standalone procedures, the sequential or simultaneous application of some different methods has also been scrutinized [9]. The combined pretreatment has been of high popularity owing to better efficiencies in terms of sludge hydrolysis, solubilization of organic constituents, biogas and methane yield, compared to when these methods are applied alone [54,161,[200][201][202]. Additionally, coupling of single pretreatments in some cases, enables the improvement of some limitations that occur during the implementation of individual methods, which are usually associated with increased energy consumption, high capital, investment and operation costs [12].…”
Section: Combined Pretreatment Methodsmentioning
confidence: 99%
“…The order the pretreatment methods are applied also affects the overall effectiveness. In the study of Mostafa et al [201], it was demonstrated that by altering the sequence of thermal-ultrasonic pretreatment set, solubilization was positively affected, presenting a surplus increment of 4%. That was assigned to ultrasonication, which led to a bulkier solids content than that resulted when it was not applied prior to thermal pretreatment, thereby increasing the availability of compounds for heating.…”
Section: Combined Pretreatment Methodsmentioning
confidence: 99%
“…With the agreement of the sustainable development goals (SDGs) adopted by the United Nations (UN), all ecofriendly waste treatment technologies have come under the spotlight . The production of methane (CH 4 ) and hydrogen (H 2 ) from organic-containing waste/wastewater, through anaerobic digestion (AD) and dark fermentation (DF) processes, is widely perceived as an efficient and sustainable treatment strategy promoting bioenergy recovery. Basic knowledge about AD and DF often refers to their drawbacks, i.e., slow microbial growth and limited substrate conversion efficiency, respectively. However, nanosized metal derivatives (NMDs), i.e., nanosized metals and their oxides, have unique chemical, thermal, and electrical properties that promote reaction yields . Nanosized provides a high surface to volume ratio and leads to totally different physicochemical properties compared to the corresponding material in its bulk size .…”
Section: Introductionmentioning
confidence: 99%
“…Formed NPs were washed twice using deionized water and finally were redispersed in cyclohexane.4 -Silica-coated n-Fe 3 nonylphenyl ether (Igepal CO-520) and cyclohexane were mixed using a mechanical stirrer for 15 min, and then oleic acid-coated n-Fe 3 O 4 (0.5 wt % in cyclohexane) was added. Finally, NH4 OH solution and tetraethyl orthosilicate (TEOS) were added consecutively under stirring, forming a transparent red solution of reverse microemulsion. A period of 16 h was required for completing this reaction.…”
mentioning
confidence: 99%
“…Refinery excess sludge (RES) accounts for 0.3-0.5% of the total treatment wastewater quantity, the moisture content is usually approximately 95%, and the production in China is 300 × 10 4 t/y [2]. Moreover, the cost of sewage sludge treatment and disposal is over half of the total cost of wastewater treatment plants [3]. The sludge usually contains considerable amounts of toxic and harmful substances, such as parasite eggs, pathogenic microorganisms, heavy metals, and unstabilized organic matter [4,5].…”
Section: Introductionmentioning
confidence: 99%